Pengolahan Tumbuhan Obat Menjadi Obat Tradisional Pada Masyarakat Desa Penyambaran Kecamatan Karang Intan Kabupaten Banjar - Arnida Arnida; Fadlilaturrahmah Fadlilaturrahmah; Annisa Sulistyowati; Nabila Nabila; Hermalia Putri; Rizka Putri Salsabila (BADAN PENERBIT STIEPARI PRESS, 2023)
The use of traditional medicine by the community is generally only in the form of a decoction, this method is considered less effective and practical because the heating temperature is not controlled which can cause damage to the compounds in the plant. The service was conducted to increase the interest and skills of the community in Penyambaran Village, Karang Intan Subdistrict, Banjar Regency, South Kalimantan Province on processing techniques and how to make good traditional medicine. The results showed an increase in community understanding with an average Post-test of 89.583 compared to an average Pre-test of 45.833. This shows that socialization has been able to increase community interest and understanding related to plants that can be used as traditional medicine, processing, packaging, storage, and drug registration.